A organização da atividade de ensino dos professores que ensinam matemática nos anos iniciais para promover a aprendizagem dos alunos em situação de vulnerabilidade social - Silva, Maria Vanusia De Oliveira [UNIFESP] (2020)
This research explores the movement of the senses associated by math teachers who teach in the early years to the organization of teaching activities aimed at promoting learning for the student who faces social vulnerability. It is based on contributions from the Cultural-historical Theory, the Theory of Activity and the concept of Teaching Guiding Activity (TGA), used as grounds in the process of learning and teaching development. To comprehend the movement of teachers' senses concerning the organization of the teaching activity that promotes the learning activity of students who deal with situations of social vulnerability, we chose the dialectical historical materialism as a method of investigation, through a formative experiment using an extension course for math teachers from the early grades of elementary school. The data analysis was structured in the isolateds "Relations between the teaching of mathematics and the context of social vulnerability: initial meanings" and "The organization of teaching and the learning difficulties resulting from social vulnerability". In discussions involving the concepts of social vulnerability, TGA, development of Triggering Situations of Learning (TSLs), reports of their development in the classroom, actions, interventions and mediations, we looked for signs of a movement of change in the organization of the teaching activity in order to promote the learning of socially vulnerable students. The results of the research indicate that, from the appropriation of the elements of the Teaching Guiding Activiy, the teachers begin to conceive this concept as a way of organizing activities and enhancing learning. The TSL emerges as a methodological resource for the teaching of mathematics that bring a triggering problem, presents a necessity and a purpose for students, with the potential to benefit the appropriation of concepts, in particular, promoting apprenticeship for children who live in a context of social vulnerability. The data revealed that the students were involved in the learning activities from the development of the TSLs, which allows us to conclude that the socially vulnerable student can, even in the face of his conditions, have his learning encouraged. Although the school does not have tools to overcome the social condition of its students, a movement of the educational organization can offer learning conditions when considering the specificity of the difficulties linked to the social vulnerability of its students, so that this condition will not be decisive in their learning processes.